Vaginal Microbiota Profile in first-trimester miscarriages cases: Vaginal Microbiota, First-trimster Miscarriage, Molecular Profile - Abdulla, Saman Rafeeq; Kareem, Sarmad Raheem; Hasan, Ayad H. (Cellular and Molecular Biology, 2023)
Due to its rising prevalence, first-trimester miscarriage is getting more attention. Abortion etiology and pathology, especially in non-pathological cases, are unknown. In this study, 435 vaginal swabs were collected from aborted women in Maternity Teaching Hospitals in Erbil and Shahid Dr. Khalid Hospital in Koya. We characterized the vaginal microbiota diversity and composition in first-trimester abortion and investigated the association between bacterial vaginosis and abortion before 12 weeks. Cultural, morphological, and biochemical characteristics for each bacterial genus were discovered, and VITEK-2 system was used to identify isolated bacteria. Samples from each type of bacteria were selected for sequencing utilizing 16 rRNA genes examining V4–V8 region for bacterial profiles. Bacterial vaginitis was found in 412 (94.7%) first-trimester miscarriages. Six Gram-positive and four Gram-negative bacteria were found in these 412 samples. Microorganism distribution varied Gram-positive bacteria Staphylococcus aureus (86) 20.87%, Enterococcus faecalis (31) 7.52%, Gardnerella vaginalis (24) 5.83%, Streptococcus agalactia (21) 5.1%, Lactobacillus equicursoris (14) 3.4% and Staphylococcus haemolyticus (12) 2.91%. Gram-negative bacteria including E. coli (107) 25.97%, Klebsiella pneumonia (76) 18.45%, Pseudomonas aeruginosa (29) 7.04% and Proteus mirabilis (12) 2.91%. Staphylococcus aureus had the highest rate of isolation at (86) 20.87%, while Lactobacillus equicursoris had the lowest rate at (14) 3.4%. Overall, the rate of isolation for Gram-negative bacteria (224) was 54.4%, while the rate for Gram-positive bacteria (188) was 45.6%.